Comparison of the Cost-utility Analysis of Electroacupuncture and Nonsteroidal Antiinflammatory Drugs in the Treatment of Chronic Low Back Pain - Mahdi Toroski; Shekoufeh Nikfar; Mohammad Mahdi Mojahedian; Mohammad Hosein Ayati (Medical Association of Pharmacopuncture Institute, 2018)
Introduction and objective: Chronic low back pain (CLBP) is among the most common and important reasons for visiting a spine surgeon by patients; it is the second cause of visiting a doctor. Low back pain can cause considerable suffering and is a major financial burden in the society. There are many different methods available for the treatment of CLBP. This study aimed to compare the cost-utility of electroacupuncture (EA) and nonsteroidal antiinflammatory drugs (NSAIDs), as two common treatment methods for patients with CLBP. Methods: This study was conducted on 100 patients suffering from CLBP. Cases were randomly selected from patients referring to two hospitals and four acupuncture clinics in Tehran. Forty-one patients received EA, and 59 patients were prescribed NSAIDs. The EuroQol five dimensions questionnaire was used to calculate quality-adjusted life-year. For calculating the total cost of the two treatment methods, face to face interview with patients was conducted by the researchers (using specific basic literature questionnaire), neurologists, and spine surgeons. The study perspective was social (direct and indirect costs calculated). Results: The mean age for EA group was 41 ± 2.3 years, and for NSAIDs group, it was 38.0 ± 4.4 years. The average of the utility of patients under treatment by EA and NSAIDs was estimated as 0.70 and 0.627, respectively. The difference in utility between the two groups was significant (p ≤ 0.05). The total cost of EA and NSAIDs was estimated as 461.48 ± 57.8$ and 497.77 ± 85.2$ for one year (2016), respectively, which was also significant (p ≤ 0.05). Conclusion: The results indicate a significant difference between EA and NSAIDs in cases of both utility and total cost. The findings demonstrate that EA is more cost-effective than NSAIDs, as therefore can be considered as an alternative treatment for CLBP, with reasonable cost-utility. Keywords: chronic low back pain, cost-utility, electroacupuncture, nonsteroidal antiinflammatory drugs